2012
DOI: 10.1051/parasite/2012194351
|View full text |Cite
|
Sign up to set email alerts
|

Differential tissular distribution ofLitomosoides sigmodontismicrofilariae between microfilaremic and amicrofilaremic mice following experimental infection

Abstract: Filariases are caused by onchocercid nematodes that are transmitted by arthropod vectors. More than 180 million people are infected worldwide. Mass drug administration has been set up in many endemic areas to control the parasite burden. Although very successful in limiting microfilarial load, transmission has not been completely interrupted in such areas. A proportion of infected patients with lymphatic filariasis or loiasis are known to be amicrofilaremic, as they do not present microfilariae in their bloods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…infections in Neotropical bats have been frequently reported [5], it is surprising that no one has ever attempted to identify the effect of this parasite on bats. Conversely, in murine models, pathological effects have been well described [21]. A study in cotton rats ( Sigmodon hispidus ), naturally infected with L. sigmodontis , found histological characteristics different from those observed in this study.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…infections in Neotropical bats have been frequently reported [5], it is surprising that no one has ever attempted to identify the effect of this parasite on bats. Conversely, in murine models, pathological effects have been well described [21]. A study in cotton rats ( Sigmodon hispidus ), naturally infected with L. sigmodontis , found histological characteristics different from those observed in this study.…”
Section: Discussioncontrasting
confidence: 88%
“…Unlike in our study where the most common vascular lesion was hypertrophy of the medial layer, in most studies in dogs with dirofilariosis, the most common were hyperplasia and hypertrophy of the capillary endothelium [25,26,27]. In a murine model infected with L. sigmodontis , Mf presence inside blood vessels of the lungs was proposed as an anatomic reservoir site during the patency of the disease [21]. The same study further proposed the said vessels as sites for larvae elimination, in addition to the spleen and liver [21].…”
Section: Discussionmentioning
confidence: 79%
“…Changes in lung tissue or in the pleura lining the thoracic cavity, the tissue with the closest contact with larvae and adult worms are less documented. The immune response in the thoracic cavity between the two pleurae has been extensively characterized at different stages of the filarial infection from the arrival of L3 larvae in the pleural space to the patent phase in susceptible (BALB/c) and resistant (C57BL/6) mouse models [ 15 , 29 , 31 , 43 – 45 ]. Depending on the mouse strain, the mode of infection (natural through the vector or inoculation of a known number of L3) and the amount of the inoculum, the intensity of cell recruitment and the secretions of specific cytokines are different [ 25 , 29 , 46 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to these granulomas, the inflammatory reaction recruits cells to the pleural cavity as early as the L3 arrive there [ 28 , 29 ]. These infiltrates are mainly composed of macrophages, neutrophils and eosinophils [ 30 ] with a peak 30 days post-infection [ 31 ]. The proliferation and the alternative activation of these pleural macrophages is promoted by the interleukin (IL)-4 receptor and IL-33 (ST2) in L. sigmodontis infected BALB/c mice [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…One could argue that some L3 within the inoculums may be unviable, but it mainly suggests that the control of the filarial load does not only take place in the skin. Previous studies indeed revealed that among the 70% of larvae that are leaving the skin within the first day, only one third are reaching the pleural cavity [ 56 ] with some L3 being found in pulmonary alveoli and arteries [ 56 ] suggesting that the lung could act as a clearance organ [ 57 ]. Of importance and in line with this, the IV infection setting experimentally supported for the first time the Wenk’s early hypothesis that the infective larvae might pass through the cardiopulmonary blood system to reach the pleural cavity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%